The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.2.22558/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A policy Analysis of Phenylketonuria Screening National Program in Iran

Abstract: Background Phenylketonuria (PKU) Screening is a public health measure aimed at identifying the early cases and managing the affected infants and trying to reduce infant morbidity and mortality. The aim of this study was to analyze the policies of the PKU national screening program in Iran. Methods PKU screening program policies were analyzed according to the policy triangle model. Document review and 38 semi-structured interviews were used for data collection. Document review data were analyzed using content a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…National and local leadership, as well as a shared vision among organizations and accountability, are strategies for the implementation of health in all policies (Guglielmin, Muntaner, Campo, & Shankardass, 2018). The implementation approach in the current research was shown to be top‐down, which is in line with other similar policy analysis in Iran (Heidari, Arab, & Damari, 2020; Loloei et al, 2019; Mohseni et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…National and local leadership, as well as a shared vision among organizations and accountability, are strategies for the implementation of health in all policies (Guglielmin, Muntaner, Campo, & Shankardass, 2018). The implementation approach in the current research was shown to be top‐down, which is in line with other similar policy analysis in Iran (Heidari, Arab, & Damari, 2020; Loloei et al, 2019; Mohseni et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…They argue, based on prior policy analysis in different contexts, that only content is not sufficient to define a policy reform; therefore, actors in different levels, not just the state, followed by how the approach is described within the form of process and context delivers supplemental data which is critical in policy reform (Walt & Gilson, 1994). The adaptation of the triangle model, which is commonly used in policy analysis (such as Mokitimi et al, 2018 and Heidari et al, 2021), provides a simple model to enable researchers and policymakers to understand better the process of policy reform in the context of developing countries (Walt & Gilson, 1994). To be able to offer a pathway to national and local policymaking from a comprehensive perspective, we modified their model at the sub‐focus level accumulated under each area based on a prior research (Ataol et al, 2019), which reports results from a systematic literature review on children's participation in urban planning and design, highlighting four critical aspects of children's participation (Figure 1): (1) content (conceptualisation of children), (2) context (approaches in participatory decision‐making), (3) actors (roles and relations in promoting participatory decision‐making) and (4) process (initiatives and projects promoting children's participation).…”
Section: Methodsmentioning
confidence: 99%
“…To add to the data consistency, the data were analyzed by various researchers and external observers. To increase verifiability, the whole research process was explained from beginning to end [17][18][19].…”
Section: Qualitative Studymentioning
confidence: 99%